Social responsibility and higher education: just a market target or a real educational challenge? An answer from the trenches - Maite Ines Jiménez; Gladys Antonia Jiménez; Carmen Márquez; Carolina Astudillo; Loreto Morales; Lorena González; Jonathan Hermosilla (University of Johannesburg, 2018)
Currently, the globalization of local problems is both surprising and concerning, as the systemic impact of these problems undermines local territories and directly affects people and the environment. As these issues are inevitable, public and private initiatives have tried to find intercontinental socially responsible solutions to fight pollution, poverty and corruption, among other problems. In this sense, it is possible to find in South America a fertile field to grow awareness, but sometimes this useful marketing resource is unable to reach students within the classroom or change their views of their future professional practice. In this way, social responsibility coexists with academic capitalism practices. This article aims to show how anchoring learning in social responsibility and ethics can transform the classroom. From the students' narratives, it can be observed that they changed their view of their professional role and transformed their discourses, integrating consideration of others into their thinking. The results lead us to question how universities influence the way in which their graduates affect the world and vice versa. The classroom, a critical, reflexive and transforming space, is the field in which this question can be answered. How to cite this article: JIMÉNEZ, Maite; JIMÉNEZ, Gladys; MÁRQUEZ, Carmen; ASTUDILLO, Carolina; MORALES, Loreto; GONZÁLEZ, Lorena; HERMOSILLA, Jonathan. Social responsibility and higher education: just a market target or a real educational challenge? An answer from the trenches. Scholarship of Teaching and Learning in the South v. 2, n. 2, p. 71-89, Sept. 2018. Available at: http://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=37&path%5B%5D=26 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/